Tax Administrative Jurisdiction Case Study Tax Court Number 86615/PP/M.XIVA/15/2017 - Wafa Alfia; Siti Nur Annisa; Abdul Latif; Ronald Kristian Hindom; Kanesa Kanesa (West Science Law and Human Rights, 2023)
Taxes are mandatory contributions to the state owed by individuals or entities that are coercive based on the law, by not getting compensation directly and used for the needs of the state for the greatest prosperity of the people. Tax payment is a form of embodiment of state obligations and the participation of taxpayers to directly and jointly carry out tax obligations for state financing and national development. This study uses a normative juridical approach, where law is conceptualized as what is written in laws and regulations (law in books) or law is conceptualized as rules or norms which are benchmarks for human behavior that are considered appropriate. This research is a form of descriptive qualitative research. Qualitative research is research that intends to understand phenomena about what is experienced by research subjects such as behavior, perceptions, motivations, actions, etc., holistically, and by describing in the form of words and language, in a specific context that naturally and by utilizing various natural methods. In this case the discussion regarding the tax report between the appellant, namely the taxpayer, and the appealed person, namely the Director General of Taxes or a tax agency and the auditor as a tax office officer. The problem started with the appellant providing data on the amount of tax to be paid by the applicant of 41,117,337,279.00. The data came from the financial reports provided to the IDPL auditor report.